TIPOLOGI TRANSFER PENGETAHUAN DALAM SUKSESI BISNIS KELUARGA UD SARI MURNI JENANG LASIMUN TULUNGAGUNG - Andi, Andi; Nurohman, Dede (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2022)
This study aims to determine how the transfer of knowledge is carried out by UD. Sari Murni (Jenang P. Lasimun), one of the SME-scale family companies in Tulungagung that can survive and thrive until the third generation. This research uses a qualitative approach with a case study method. The object of this research is a family company and the subjects used are the predecessor generation, potential successors, employees and permanent consumers. Data collection techniques using observation and in-depth interviews. The results of the study found that there was some knowledge that was transferred by the previous generation to the successor, including product knowledge, company management knowledge, technical knowledge and philosophical knowledge. Knowledge transfer is given to all children of the predecessors in each generation from an early age and the selection of the next successor through the fourth of transferred knowledge typology.